Altered Monocyte Populations and Activation Marker Expression in Children with Autism and Co-Occurring Gastrointestinal Symptoms - Rachel J. Moreno; Yasmin W. Azzam; Serena Eng; Destanie Rose; Paul Ashwood (Biomolecules)
Autism spectrum disorder (ASD) is an early-onset neurodevelopmental condition that now impacts 1 in 36 children in the United States and is characterized by deficits in social communication, repetitive behaviors, and restricted interests. Children with ASD also frequently experience co-morbidities including anxiety and ADHD, and up to 80% experience gastrointestinal (GI) symptoms such as constipation, diarrhea, and/or abdominal pain. Systemic immune activation and dysregulation, including increased pro-inflammatory cytokines, are frequently observed in ASD. Evidence has shown that the innate immune system may be impacted in ASD, as altered monocyte gene expression profiles and cytokine responses to pattern recognition ligands have been observed compared to typically developing (TD) children. In humans, circulating monocytes are often categorized into three subpopulations—classical, transitional (or “intermediate”), and nonclassical monocytes, which can vary in functions, including archetypal inflammatory and/or reparative functions, as well as their effector locations. The potential for monocytes to contribute to immune dysregulation in ASD and its comorbidities has so far not been extensively studied. This study aims to determine whether these monocyte subsets differ in frequency in children with ASD and if the presence of GI symptoms alters subset distribution, as has been seen for T cell subsets. Whole blood from ASD children with (ASD+GI+) and without gastrointestinal symptoms (ASD+GI−) and their TD counterparts was collected from children enrolled in the Childhood Autism Risk from Genetics and Environment (CHARGE) study. Peripheral blood mononuclear cells were isolated and stained for commonly used subset identifiers CD14 and CD16 as well as activation state markers CCR2, HLA-DR, PD-1, and PD-L1 for flow cytometry analysis. We identified changes in monocyte subpopulations and their expression of surface markers in children with ASD compared to TD children. These differences in ASD appear to be dependent on the presence or absence of GI symptoms. We found that the ASD+GI+ group have a different monocyte composition, evident in their classical, transitional, and nonclassical populations, compared to the ASD+GI− and TD groups. Both the ASD+GI+ and ASD+GI− groups exhibited greater frequencies of classical monocytes compared to the TD group. However, the ASD+GI+ group demonstrated lower frequencies of transitional and nonclassical monocytes than their ASD+GI− and TD counterparts. CCR2+ classical monocyte frequencies were highest in the ASD+GI− group. HLA-DR+ classical, transitional, and nonclassical monocytes were statistically comparable between groups, however, HLA-DR− nonclassical monocyte frequencies were lower in both ASD groups compared to TD. The frequency of classical monocytes displaying exhaustion markers PD-1 and PD-L1 were increased in the ASD+GI+ group compared to ASD+GI− and TD, suggesting potentially impaired ability for clearance of foreign pathogens or debris, typically associated with worsened inflammation. Taken together, the findings of differential proportions of the monocyte subpopulations and altered surface markers may explain some of the characteristics of immune dysregulation, such as in the gastrointestinal tract, observed in ASD.